Cherax (Astaconephrops) gherardii, a new crayfish (Decapoda: Parastacidae) from West Papua, Indonesia - Patoka, Jiří; Bláha, Martin; Kouba, Antonín (Zootaxa, 2015)
Cherax (Astaconephrops) gherardii n. sp. is a moderate burrowing crayfish endemic to the Ajamaru Lakes of West Papua, Indonesia. This species is one of the crayfish species from this region that are exploited for ornamental purposes. Its commonly used commercial name in the pet trade is “Rainbow Crayfish” or “Blue Moon Crayfish”, and its native name is “udang kuku biru”. The new species is genetically and morphologically similar to Cherax boesemani, however, both species may be easily distinguished morphologically or by using sequence divergence, which is substantial for considering C. gherardii n. sp. to be a valid species.